(3GdGYJbGOGJs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3HGH aj UaI GYJbGOGJ GdEeGejI aj GdJhMjO, bGd GdTjN CHh LYaQ eMeO Hf Ydj Hf GdMSjf Hf ehSi Hf HGHhjg (B... (3GdeUfa dgPG GdcJGH(B: (3GYde Cf GYJbGOfG aj GdJhMjO(B...s
(3BNQgG (B:s
(3hEPG CJGfj gh ddNdhI hCbGe aj HjJj hde Jbe YfG aGWeI hdG CMOG ef CHfGFj cfJ EPGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B274s
(3GdCYdGe(B: (3L(B6(3, U(B274s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds